2016
DOI: 10.3233/wor-162457
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based ergonomics education: Promoting risk factor awareness among office computer workers

Abstract: The findings have implications for injury prevention in office settings and suggest that ergonomics education may yield positive knowledge and behavioral changes among computer workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…Our current approach combines the knowledge of ergonomics and the clinical expertise of physiotherapists focusing on how to integrate this knowledge into real-life applications during the actual daily work process. The results in this study showed positive effect on the occupational exposure outcomes, which aligns with a previous study on workplace ergonomics education combined with workplace-based exercise training to office workers [13,41,42]. The improvement in both subjective job related physical demand and workstyle may be an indicator of the positive knowledge and successful behavioral changes among the workers [42].…”
Section: Integrating Ergonomics and Motor Control Interventionssupporting
confidence: 89%
“…Our current approach combines the knowledge of ergonomics and the clinical expertise of physiotherapists focusing on how to integrate this knowledge into real-life applications during the actual daily work process. The results in this study showed positive effect on the occupational exposure outcomes, which aligns with a previous study on workplace ergonomics education combined with workplace-based exercise training to office workers [13,41,42]. The improvement in both subjective job related physical demand and workstyle may be an indicator of the positive knowledge and successful behavioral changes among the workers [42].…”
Section: Integrating Ergonomics and Motor Control Interventionssupporting
confidence: 89%
“…Some of the WMSD prevention strategies in practice include workstation modification, task modification, and provision of necessary ergonomic accessories. However, "for these prevention measures to work, proper knowledge/awareness about how (a) the work-related factors contribute to WMSDs, (b) to carry out the work tasks safely, and (c) to effectively use the equipment, are essential" [13]. Robertson et al [29] stated that the availability of adjustable office furniture alone cannot reduce or prevent musculoskeletal injuries.…”
Section: Prevention Of Work-related Musculoskeletal Disordersmentioning
confidence: 99%
“…Hence, to prevent WMSDs among OCWs and ensure their well-being, it is critical to educate them on "ergonomics" and "risk factors associated with WMSDs." An evidence-based strategy to impart this education is Ergonomics Education [13,30].…”
Section: Prevention Of Work-related Musculoskeletal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos, a su vez, podían comprender ejercicios posturales y de estabilización articular cervical y/o lumbar. El programa de ejercicios contenía actividades tanto de pie como sentado (5,25,26) .…”
Section: Folletos Informativos Más Pausas Activas Supervisadasunclassified